2001
DOI: 10.2337/diacare.24.6.1093
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Inhibition Ameliorates Pupillary Light Reflex and F-Wave Latency in Patients With Mild Diabetic Neuropathy

Abstract: OBJECTIVE -The present study was conducted to investigate the effect of an aldose reductase inhibitor, epalrestat, on autonomic and somatic neuropathy at an early stage in type 2 diabetic patients by assessing the pupillary light reflex and minimum latency of the F-wave. RESEARCH DESIGN AND METHODS-A total of 30 diabetic patients with subclinical or mild diabetic neuropathy were randomly allocated to a control group (n ϭ 15) and epalrestat (150 mg/day) group (n ϭ 15). After 24 weeks, the pupillary light reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…In our study, epalrestat was associated with a significantly shorter MFWL of the median motor nerve compared with the control group, which is in agreement with another study with mild neuropathy (17). Other ARIs, including fidarestat, ranirestat, and zenarestat, have also been reported to improve MNCV and MFWL.…”
Section: Safetysupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, epalrestat was associated with a significantly shorter MFWL of the median motor nerve compared with the control group, which is in agreement with another study with mild neuropathy (17). Other ARIs, including fidarestat, ranirestat, and zenarestat, have also been reported to improve MNCV and MFWL.…”
Section: Safetysupporting
confidence: 92%
“…MFWL may also be a useful index to evaluate diabetic neuropathy (17,18). In our study, epalrestat was associated with a significantly shorter MFWL of the median motor nerve compared with the control group, which is in agreement with another study with mild neuropathy (17).…”
Section: Safetysupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to demonstrate a correlation between erythrocyte sorbitol levels and changes in nerve function tests during ARI administration. Nakayama et al (2001) have reported that 24 weeks of epalrestat treatment ameliorated papillary light reflex and F-wave latency, but not nerve conduction velocity, in patients with mild diabetic neuropathy. On the other hand, ARI, zenarestat, has shown to reduce both erythrocyte and nerve sorbitol contents in a dose-dependent manner and that this sorbitol suppression was accompanied by significant improvements in the slowing down of nerve conduction velocity and the loss of small myelinated nerve fibers in patients with diabetic polyneuropathy (Greene, Arezzo, & Brown, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in nerve function and in upper limb symptoms suggest the potential for clinically significant drug effect, which is currently being studied in Phase III trials [25].…”
Section: B Selective Inhibition Of the Polyol Pathway With Aldose Rementioning
confidence: 99%